Peningkatan Motivasi Belajar Membaca Al Quran Menggunakan Model PBL di Kelas IV UPTD SDN 03 Bangkok - Masroh, Masroh (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The Quran is the primary source of guidance for Muslims, and learning to read it correctly is essential for understanding its teachings. However, many students struggle with recognizing the Arabic letters (huruf hijaiyah), applying tajwid rules, and reading the Quran properly. These challenges, combined with a lack of motivation and inadequate parental support, hinder the development of Quranic reading skills among students. This research aims to improve students’ motivation and skills in reading the Quran through the application of the Problem-Based Learning (PBL) model in the 4th grade at UPTD SD Negeri 03 Bangkok. The study identifies several key factors affecting students’ learning, including limited time allocation for Quranic learning, insufficient parental involvement, low student motivation, and ineffective teaching methods. By implementing the PBL model, the study aims to create a more engaging and effective learning environment, thereby increasing students’ interest and proficiency in reading the Quran. This action research seeks to explore how PBL can enhance students’ motivation and provide a more meaningful and contextual learning experience. The results of the study are expected to contribute to improving Quranic literacy in schools and highlight the importance of innovative teaching approaches in fostering spiritual and academic growth.